Affordable reliability engineering life-cycle cost analysis for sustainability & logistical support - Wessels, William R.; Sillivant, Daniel S. (CRC Press, 2015)
The text is based on the premise that all system sustainment costs result from part failure. It examines part failure in the design and sustainment of fielded parts and outlines a design criticality analysis procedure that reflects system design and sustainment